ANALYSIS OF GOVERNMENT EXPENDITURE AND COMMUNITY WELFARE - Gaffar, Elvyani Nuri Harlawati (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This research is to analyze government expenditure and community welfare. The research method used in this study uses a design that is a literature review. A literature review is a research conducted by collecting various references or journals related to the research problem. The literature review is used to describe various theories that are relevant to the problems studied to be used as reference material for discussing research results. From the results of the research conducted, it can be concluded that community welfare is the final result (final goal) of development activities in an area or country, where the Human Development Index (HDI) is one of the indicators that affect community welfare. The results show that government expenditure, especially in education, health, employment (labor absorption influence on community income), and development infrastructure will able to affect the welfare of the community. This is because an increase in government expenditure on these sectors will have an impact on improving community welfare to achieve a better standard of living.